2020
DOI: 10.1039/d0cp03551c
|View full text |Cite
|
Sign up to set email alerts
|

Towards molecular movies with X-ray photon correlation spectroscopy

Abstract: We highlight perspective research opportunities of making molecular movies of biomolecular condensates and supercooled water using X-ray synchrotrons and XFELs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 105 publications
(118 reference statements)
1
30
0
Order By: Relevance
“…49,50 From this perspective, it would be interesting to investigate the translational dynamics of protein hydration water by using state-of-the-art coherent X-ray scattering techniques, such as X-ray photon correlation spectroscopy. 51…”
Section: Discussionmentioning
confidence: 99%
“…49,50 From this perspective, it would be interesting to investigate the translational dynamics of protein hydration water by using state-of-the-art coherent X-ray scattering techniques, such as X-ray photon correlation spectroscopy. 51…”
Section: Discussionmentioning
confidence: 99%
“…The relevant length scales, e.g., the size of a protein, is usually in the range of few nm, thus, diffusion dynamics as fastest relevant process will extend to the sub-µs regime. Radiation-induced damage has to be considered for such samples, leading to a modified signal-to-noise ratio [37,64]. First XPCS studies on protein diffusion have been demonstrated recently using fast detectors with access to µs time scales [36,199,200].…”
Section: Biological Samplesmentioning
confidence: 99%
“…First XPCS studies on protein diffusion have been demonstrated recently using fast detectors with access to µs time scales [36,199,200]. In addition to storage-ring based XPCS, application of XSVS schemes will be applied to limit the radiation damage [65,140], as well as studies at FEL sources are foreseen using different pulse schemes [37]. Besides protein dynamics, XPCS will become possible for nanomedicine studies, such as probing nanoparticle-protein interaction which is important for drug release in cellular environments [201].…”
Section: Biological Samplesmentioning
confidence: 99%
See 1 more Smart Citation
“…The evolution of dynamics is obtained from the two-time correlation (TTC) defined as the covariance of the scattered intensity [12,13,[29][30][31][32][33][34][35]…”
mentioning
confidence: 99%